The impact of pre-operative axial length on myopic shift 3 years after congenital and developmental cataract surgery and intraocular lens implantation - Zhou, Xiyue; Fan, Fan; Liu, Xin; Yang, Jianing; Yang, Tianke; Luo, Yi (Frontiers in Medicine, 2023)
Purpose: To investigate the impact of the preoperative axial length (AL) on myopic shift (MS) 3 years after primary intraocular lens (IOL) implantation in congenital/developmental cataract patients. Methods: A retrospective study of patients who underwent congenital/developmental cataract surgery and primary IOL implantation at age 2-3 years at EENT Hospital was conducted. All patients were followed up regularly for at least 3 years after surgery. Refractive outcomes, including spherical equivalent (SE) and MS, were collected at each follow-up. Results: Forty eyes from 40 patients were included. The mean age at surgery was 2.56±0.57 years old, and the mean follow-up time was 3.05± 0.22 years. Patients were divided into two groups: Group 1 included 20 patients with longer preoperative ALs (≥22 mm), and Group 2 included 20 patients with average preoperative ALs (<22 mm). By the last follow-up, the MS was 2.13 (0.38, 2.63) D in Group 1 and 3.88 (2.85, 5.72) D in Group 2. The postoperative MS in Group 2 was statistically greater than that in Group 1 at 3 years after surgery (P<0.001). Conclusion: In congenital/developmental cataract patients who underwent cataract extraction and primary IOL implantation at age 2-3 years, eyes with longer preoperative ALs had a slower MS than those with average preoperative ALs 3 years after surgery. This finding could have implications for the target refraction decision in congenital/developmental cataract surgery.